LEARNING BASED ON SCIENTIFIC APPROACH ASSISTED BY TEXTBOOK OF â€œAKU DAN FISIKAâ€ IN DYNAMIC ROTATION AND BALANCED MATERIAL TO IMPROVE LEARNING OUTCOMES - WINARSIH, DEFI (Inovasi Pendidikan Fisika, 2018)
This study is aimed to describe the average learning outcomes of using scientific approach assisted by Aku dan Fisika textbook is better than learning by lecture method. The learning outcomes of XI MIA students of SMA Muhammadiyah 2 Surabaya can be increased after applying scientific approach learning assisted by textbook Aku dan Fisika. True experimental design isused in this study. One experimental class is XI MIA 2 and one control class is XI MIA 3. The results show that the learning using scientific approach assisted by Aku dan Fisika textbook is better than the learning of lecture method. The knowledge of students in experimental class increases and it is considered as high category. While in the control class increases and it is considered as medium category. Value of students’ skills in experimental classes is 3,23 with category B+. The highest attitudes gained in both classes are the gratitude and meticulous attitude with the excellent category while the differentiating attitude between the two classes is the active attitude of asking. So it can be concluded that the average learning outcomes of using scientific approach assisted by Aku dan Fisika textbook is better than the learning of lecture method and the learning outcomes of XI MIA students of SMA Muhammadiyah 2 Surabaya can be increased after applying scientific approach learning assisted by Aku dan Fisika in center mass material. Keywords: scientific approach, dynamic rotation, balanced.